2023
DOI: 10.3389/fcell.2023.1257651
|View full text |Cite
|
Sign up to set email alerts
|

MYC—an emerging player in mitochondrial diseases

Janne Purhonen,
Juha Klefström,
Jukka Kallijärvi

Abstract: The mitochondrion is a major hub of cellular metabolism and involved directly or indirectly in almost all biological processes of the cell. In mitochondrial diseases, compromised respiratory electron transfer and oxidative phosphorylation (OXPHOS) lead to compensatory rewiring of metabolism with resemblance to the Warburg-like metabolic state of cancer cells. The transcription factor MYC (or c-MYC) is a major regulator of metabolic rewiring in cancer, stimulating glycolysis, nucleotide biosynthesis, and glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…The MYC gene, as an important transcription factor, plays a key role in processes such as cell proliferation, differentiation, and apoptosis. [ 15 , 16 ] Currently, foreign literature has extensively studied the relationship between the MYC gene and colorectal cancer. Previous studies have shown that abnormal expression of the MYC gene is closely related to the occurrence and development of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The MYC gene, as an important transcription factor, plays a key role in processes such as cell proliferation, differentiation, and apoptosis. [ 15 , 16 ] Currently, foreign literature has extensively studied the relationship between the MYC gene and colorectal cancer. Previous studies have shown that abnormal expression of the MYC gene is closely related to the occurrence and development of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies link MYC to a range of other disorders, mainly through experiments to determine its expression in model systems or patients. In particular—and not surprisingly—there are strong suggestions of a role in endometriosis ( Nothnick et al, 2023 ), mitochondrial diseases ( Purhonen et al, 2023 ), immune-related, neurodegenerative and other metabolism-related diseases. These are summarised in Table 1 with some of the data hinting at a role for MYC.…”
Section: Myc’s Involvement In Diseases and Conditionsmentioning
confidence: 99%